2014
DOI: 10.1371/journal.pone.0093859
|View full text |Cite
|
Sign up to set email alerts
|

Comparing Population Patterns to Processes: Abundance and Survival of a Forest Salamander following Habitat Degradation

Abstract: Habitat degradation resulting from anthropogenic activities poses immediate and prolonged threats to biodiversity, particularly among declining amphibians. Many studies infer amphibian response to habitat degradation by correlating patterns in species occupancy or abundance with environmental effects, often without regard to the demographic processes underlying these patterns. We evaluated how retention of vertical green trees (CANOPY) and coarse woody debris (CWD) influenced terrestrial salamander abundance a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
16
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 20 publications
(16 citation statements)
references
References 50 publications
0
16
0
Order By: Relevance
“…Generally, salamander richness and abundance were positively correlated with stand age (North Carolina, Petranka et al 1994; Oregon and Washington, Kroll et al 2008). When mature forest was clearcut, salamander populations were dramatically reduced, or emigrated into the soil profile or out of the harvest area where they were not detectable (Petranka et al 1994, Semlitsch et al 2008, Otto et al 2014). After the effects of the initial disturbance, populations slowly increased over time (Petranka et al 1994).…”
Section: Clearcuttingmentioning
confidence: 99%
See 2 more Smart Citations
“…Generally, salamander richness and abundance were positively correlated with stand age (North Carolina, Petranka et al 1994; Oregon and Washington, Kroll et al 2008). When mature forest was clearcut, salamander populations were dramatically reduced, or emigrated into the soil profile or out of the harvest area where they were not detectable (Petranka et al 1994, Semlitsch et al 2008, Otto et al 2014). After the effects of the initial disturbance, populations slowly increased over time (Petranka et al 1994).…”
Section: Clearcuttingmentioning
confidence: 99%
“…For downed wood and canopy cover, effect sizes of the relationships tended to be imprecise (Otto et al 2013), suggesting that other factors affect salamanders. Although few studies have evaluated relationships between amphibian vital rates and structural retention, terrestrial salamander survival was positively related to canopy and downed wood retention in Michigan (Otto et al 2014). Similarly, abundances of ensantina (Ensatina eschscholtzii) and clouded salamanders (Aneides ferreus)…”
Section: Managing Coarse Woody Debris During Final Harvestmentioning
confidence: 99%
See 1 more Smart Citation
“…Thus, without close examination of relationships between these groups, one could have interpreted erroneously that a pattern existed in salamander responses to a broader context, including herbaceous plants. Finally, despite their abundance, terrestrial salamanders often have low or variable detection and recapture rates, as well as small body sizes, factors that complicate tracking individuals and quantifying population responses accurately [79,[92][93][94][95]. …”
Section: Salamanders As Barometers Of Forest Conditionmentioning
confidence: 99%
“…Annual survival of P. hongkongensis increased with greater extent of forest cover around breeding pools, suggesting that this factor was a strong indicator of the quality of core terrestrial habitat. Previous studies have demonstrated impacts of forest clearance on survivorship of amphibians (Connette & Semlitsch, ; Otto, Roloff, & Thames, ; Rittenhouse, Harper, Rehard, & Semlitsch, ; Rothermel & Semlitsch, ; Todd & Rothermel, ) and consequential increases in risk of population extinction where forest cover has been reduced substantially (Harper, Rittenhouse, & Semlitsch, ), as well as life stage‐specific responses to different timber management practices (Semlitsch et al., ). As population dynamics in longer‐lived amphibians, such as P. hongkongensis , are mediated largely by the survival of adults (Berven, ; Gill, ; Wilbur, ), protection of undisturbed forests around breeding sites is essential for population viability.…”
Section: Discussionmentioning
confidence: 99%